Seasonal variation in characteristics of underground irrigation waters and their influence on soils (Indian Journal of Arid Horticulture, 2025)
Two sets of well water were collected, one before the monsoon rains in the month of April-May and second after the cessation of monsoon rains in the month of October. After the rains, salt concentration in the well water was reduced. Soil samples were also collected from areas irrigated by water of some of these wells, and analysed to study the effect of continuous use of irrigation water on them. Amount of salt retained in soil after the rains was linearly related to initial salinity in the soil. Being low rainfall in the studied area, the negative values of salt regime constant'd' were also of very low order indicating very less leaching of salts from the crop root zone and thus, continuous use of higher salinity water might hinder the crop production.
Keywords: seasonal variation; underground irrigation waters; influence on soils